Institusionalisasi Internal Audit Capability Model (IACM) Pada Aparat Pengawas Intern Pemerintah (APIP) Kementerian Luar Negeri - Tyarlin Maryani (Journal of Social and Political Science)
This study aims to understanding of the institutionalization process of the Internal Audit Capabilty Model (IACM) conducted by the APIP Ministry of Foreign Affairs with emphasis on the implementation of institutionalization process and the implications of the organization. To achieve the research objectives, the approach used is descriptive qualitative by using case study strategy. The background of the institutionalization of IACM will be analyzed using New Institutionalism Theory (NIT), and the implications of the application are analyzed using Organizational Change based on the stages of movement The result of the research shows that the institutionalization of IACM in the APIP foreign ministry has the ability to perform its roles and functions optimally in order to add value to the organization. Strategy of level 3 APIP capability improvement consists of six elements. The first element is very important for APIP Ministry of Foreign Affairs to speed up the internal audit charter. The second element, the recruitment of competent human resources, the sustainability of human resource quality improvement. The third element needs to be implemented Quality assurance. The fourth element of APIP needs to have policies, systems and procedures for reporting the management of supervisory activities and supporting accountability, the fifth element of APIP needs to participate effectively by adding value to its organization. Element 6 APIP builds a transparent budgeting process to ensure the availability of resources in the performance of tasks responsibility. keywords: IACM, APIP, Institutionalisasi, Changing organization